Private Payer Reimbursement Policy and Live‐Video Utilization for Outpatient Mental Health Care Among the Privately Insured. (20th August 2020) - Amill‐Rosario, A.; Segel, J.; Shi, Y.; Leslie, D.; Hillemeier, M.; Scanlon, D.
Abstract : Telehealth has the potential to improve access to care for patients with mental health conditions, but utilization remains low. To increase telehealth utilization, states have enacted private payer laws. While these laws appear to be associated with increased telehealth utilization, the details vary considerably from state to state. We, therefore, use longitudinal data and a codification of state telehealth private payer laws to study which aspects of the laws appear to drive the increase in utilization rates in privately insured patients with mental health disorders. We used state‐fixed effects models to estimate how policies affect live‐video utilization. We used as the dependent variable the rate of live‐video utilization per 1000 enrollees with any mental health diagnosis by state and year. Our independent variable of interest included four potential law characteristics. (a) "Full reimbursement parity"—whether telehealth services must be reimbursed at the same or equivalent rate as non‐telehealth services. (b) "Terms and conditions"—whether the law stipulates that private payers should pay and/or cover telehealth benefits based on the terms and conditions clauses of the contracts with the provider. (c) "Health services restrictions"—whether the policy explicitly states that no restrictions should apply to telehealth services or does not specify any services restrictions. (d) "Rural restriction"—whether the policy limits telehealth to rural areas only. We combined these characteristics to compare the telehealth utilization rates relative to states without telehealth private payer laws. Our models also included control variables to account for the patients' demographic characteristics, type of insurance, comorbidities, and type of provider. We analyzed 2012‐2016 Outpatient Truven Health MarketScan® Commercial Claims and Encounters data. This data set includes health coverage and outpatient services information from about 25 million employer‐sponsored plan enrollees. Our study sample includes about 5 million enrollees per year with any mental health diagnosis and younger than 65. In 2016, the telehealth utilization rates ranged from 0.12 to 12.4 per 1000 enrollees with mental health diagnosis. For most states, telehealth utilization rates increased from 2012 to 2016. In the state‐fixed effects models, states without policies had similar telehealth utilization rates compared to states with policies. However, relative to states without telehealth policies, in states with the law plus "full reimbursement parity" utilization rates increased by 2.9 per every 1000 enrollees with a mental health condition. The growth in telehealth utilization varies by state. Having telehealth private payer laws does not necessarily relate to increased utilization rates. However, explicitly requiring full reimbursement parity for telehealth services relative to non‐telehealth services lead to higher utilization rates. The evaluation of telehealth private payer policies should account for the effects of the laws' reimbursement and restrictions statutes on the telehealth utilization rates. The findings of this study could inform policy debates on regulation intended to promote telehealth utilization for patients needing mental health care.